Chaka de Senghor ou la renégociation de l’ethos préalable - Nanourougo Coulibaly (Multilinguales)
This article focuses on the mechanisms and resources implemented in the discursive confrontation between Chaka and the white voice in Senghor’s dramatic poem. It analyzes enunciation and argumentative processes used mainly by Chaka. The analysis highlights the process of rebuilding its altered public image. It demonstrates that the combination of argumentative and enunciation factors contributing to the construction of a persuasive text anchored in a self-presentation whose ultimate goal is to offer an acceptable image.